Determination of the inorganic composition and short term effect of aqueous extracts of root, pod, and stem of Telfairia occidentalis on some hematological parameters in rats - Ogbonnaya, Enyinnaya A; Uadia, Patrick O (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: This study is to investigate the inorganic composition and the effect of fourteen (14) -day oral administration of aqueous extracts of root, pod and stem of Telfairia occidentalis in rats. Materials and Methods: Plant samples were analyzed for K, P, Mg, Ca, S, Mn, Fe, Cu, Zn, Pb, and Cr using atomic absorption spectrophotometry (AAS). Wister rats of both sexes were assigned to sixteen (16) groups of 4 animals per group. Different animal groups received distilled water and root, stem, and pod extracts at the doses of 250, 750, 1500, 2250, and 3000mg/kg of body weight. All animals were treated for 14 days and sacrificed on the 15th day. Results: The inorganic composition result showed that potassium (K) was the highest in abundance in all the samples (root, pod, and stem), compared to the other mineral elements. The root contained high levels of potassium and manganese; the stem had magnesium, manganese and iron while the pod contained high amount of potassium, manganese and iron. Hematological assay results showed reduction in the values of white blood cell (WBC) count for higher doses of root extract and all doses (except for 1500mg/kg bw) of pod extract. Platelet count (PLT) was significantly high for root extract at 750mg/kg bw. The stem extract showed a consistent decrease in the red blood cell (RBC) count for all dose administered. Conclusion: Telfairia occidentalis root, pod, and stem may be a good source of inorganic elements. The extracts have varying effects on hematological parameters which may be dosage- and duration- dependent. Asian Journal of Medical Sciences Vol.7(5) 2016 75-80